Impact of the K-line in patients with ossification of the posterior longitudinal ligament: Analysis of sagittal cervical curvature changes and surgical outcomes - Tang, Zhongxin; Chen, Tailong; Tan, Jun; Zhang, Huafeng (Frontiers in Surgery, 2023)
Objective：This study aimed to investigate the relationship of K-line with sagittal cervical curvature change and surgical outcomes in patients with cervical ossification of the posterior longitudinal ligament (OPLL). Methods: We retrospectively reviewed 84 patients with OPLL who underwent posterior cervical single-door laminoplasty. The patients were divided into a K-line positive (+) group and a K-line negative (-) group. Perioperative data, radiographic parameters and clinical outcomes were compared between the two groups. Results: Of 84 total patients, 50 patients in the K (+) group, 29 patients in the K (-) group. Neurological function was improved in both groups after laminoplasty. The C2–7 Cobb angle, T1 slope, and C2–7 SVA were significantly changed in the K(−) group than the K(+) group before the operation、 at the 3-month and final follow-ups. Conclusion： Neurological function was recovered in both groups, the clinical effect in the K (+) group was better than that in the K (−) group. The cervical curvature in patients with OPLL tends to be anteverted and kyphotic after laminoplasty, which the important factor reducing clinical effect.